Preventing epilepsy after traumatic brain injury: A propensity score analysis. Issue 10 (1st October 2020) - Liou, Jaw-Horng; Chang, Yen-Lin; Lee, Hsu-Tung; Wu, Ming-Fen; Hou, Yu-Chi; Liou, Wen-Shyong
Abstract : Background: Due to the potential consequences of post-traumatic epilepsy (PTE) exacerbating secondary injury following traumatic brain injury (TBI), the use of antiepileptic drugs (AEDs) is an accepted option for seizure prophylaxis. However, there is only a paucity of data that can be found regarding outcomes surrounding the use of AEDs. The purpose of this retrospective study is to evaluate whether the prophylactic administration of AEDs significantly decreased the incidence of PTE, when considering the severity of TBI. Methods: All trauma patients who had been newly diagnosed with TBI from January 1, 2010 to December 31, 2017 were retrospectively analyzed. Statistical comparisons were made using the chi-square test, Mann-Whitney U test, and Cox regression modeling. After excluding any exposed subjects with no appropriate match, patients who had received AED prophylaxis were matched by propensity score with those who did not receive AEDs. All of the TBI populations were followed up until June 30, 2018. Results: We identified 1316 patients who met the inclusion and exclusion criteria in our matched cohort through their propensity scores, where 138 patients had been receiving prophylactic AEDs and 138 patients had not. Baseline characteristics were similar in gender, age, Glasgow Coma Scale (GCS) scores, and risk factors of PTE including skull fracture, chronic alcoholism, subdural hematoma, epidural hematoma, and intracerebral hematoma. After adjusting for those risk factors, the relative incidence of seizure was not statistically significant in either of the groups ( p = 0.566). Conclusion: In our cohort analysis, AED prophylaxis was ineffective in preventing seizures, as the rate of seizures was similar whether patients had been receiving the drugs or not. We therefore concluded that the benefits of routine prophylactic anticonvulsant therapy in patients with TBI need to be re-evaluated.